Analysis of Strength of Glass Fibre Composite Leaf Spring Using Finite Element Method - Andoko Andoko; Poppy Puspitasari; Avita Ayu Permanasari (Journal of Mechanical Engineering Science and Technology (JMEST), 2017)
Leaf spring, as one of the main components of the suspension system, serves the function of absorbing road shocks and any wheel vibrations, preventing them from being transmitted directly to the vehicle body. Moreover, it can increase the tire traction as well as support the weight of the vehicle and various kinds of external forces. Various studies on the use of composite materials for leaf springs have shown that the strength of composite leaf spring is similar to steel leaf spring with the same load carrying capacity. However, the composite leaf spring has the added advantage of being more lightweight. In fact, composite materials have been preferable for many purposes not only because of its properties but also its lightweight structure and cost effectiveness. The analysis process was carried out using the finite element method by means of ANSYS software to display the output of the analysis being performed. After the output is known, the amount of voltage in conventional, mounted, and progressive spring can be determined. Based on the data analysis, we concluded that conventional straight leaf springs produced a maximum voltage of 653.13 MPa and maximum deflection of 4367.1 mm. The results of the analysis using the finite element method showed that conventional leaf springs (both straight and not) are considered as the most effective model of leaf spring in terms of the power generated.